Preparation method and application of chlorine-free PtCu / C catalyst with hollow sphere structure

Through the preparation method of chlorine-free PtCu/C catalyst, the nano-hollow spherical PtCu particles are formed by using the strong electrostatic adsorption and impregnation reduction method of chlorine-free metal precursor and carbon support, which solves the scarcity, high cost and low stability of the existing Pt-based catalysts and improves the electrocatalytic activity and stability of the catalyst.

CN119725583AActive Publication Date: 2025-03-28KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411873567.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing Pt-based catalysts have problems of scarcity, high cost and low stability in fuel cells. At the same time, the presence of chlorides will poison the catalyst and reduce its activity and service life.

Method used

The preparation method of chlorine-free PtCu/C catalyst was adopted, and PtCu particles with nano hollow sphere structure were formed by calcining the carbon support, hydrothermal treatment and adjusting the pH, and the chlorine-free metal precursors Pt(NH3)4(OH)2 and Cu(NH3)4(OH)2 were used to perform strong electrostatic adsorption and impregnation reduction.

Benefits of technology

It improves the electrocatalytic activity and stability of the catalyst, increases the electrochemical active surface area, reduces the reaction energy barrier, reduces the toxic effect of chlorides, and extends the service life of the membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005196303620000011
    Figure HDA0005196303620000011
  • Figure HDA0005196303620000012
    Figure HDA0005196303620000012
  • Figure HDA0005196303620000021
    Figure HDA0005196303620000021
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a chlorine-free PtCu / C catalyst with a hollow sphere structure. The preparation method comprises the following steps: roasting a carbon carrier in a reducing atmosphere; dispersing the roasted carbon carrier in an alcohol-water mixed solution, and adding an oxidizing agent for hydrothermal reaction; uniformly dispersing the carbon carrier after the hydrothermal reaction in an alcohol-water mixed solution, and adjusting the pH to be acidic to obtain a carbon carrier suspension; a Pt (NH3) 4 (OH) 2 solution and a Cu (NH3) 4 (OH) 2 solution are added into the carbon carrier suspension, then a reducing agent is added for reduction, the chlorine-free PtCu / C catalyst is obtained, and PtCu is of a nanometer hollow sphere structure. According to the invention, the pollution of residual Cl ions in the existing catalyst is eliminated; through the synergistic effect and ligand effect between Pt and Cu atoms, the adsorption strength of an oxygen-containing intermediate on a Pt site in the ORR process can be weakened, and the reaction energy barrier of the catalyst in the oxygen reduction process is reduced; the high atom utilization rate and the large electrochemical activity surface area of the hollow sphere structure are also beneficial to the generation of a catalytic reaction, so that the catalyst has excellent ORR electrocatalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cell catalysts; more specifically, to a preparation method and application of a chlorine-free PtCu / C catalyst with a hollow sphere structure. Background Art

[0002] The growing global energy demand and environmental issues have driven the development of sustainable energy conversion and storage technologies. Proton exchange membrane fuel cells (PEMFCs) have attracted much attention as an efficient and pollution-free green hydrogen energy conversion technology. Pt-based catalysts are an important component of PEMFCs, which can significantly reduce the reaction overpotential and accelerate the kinetically slow oxygen reduction reaction (ORR) at the cathode. However, the scarcity, high cost and low stability of Pt have seriously hindered the large-scale commercial application of PEMFCs. Therefore, the development of Pt-based catalysts with low Pt loading, high activity and high stability is crucial to accelerate the kinetics of cathode ORR and improve the energy conversion efficiency of PEMFCs.

[0003] Alloying Pt with transition metals (Fe, Co, Ni, Cu) is an effective strategy to reduce catalyst costs. The resulting lattice strain and ligand effect can further optimize the electronic structure of Pt and improve the adsorption strength of oxygen-containing intermediates, thereby increasing the ORR catalytic activity. However, in the oxidative chemical environment of acidic electrolytes and at higher reaction potentials, transition metal (Fe or Co) dissolution problems often occur, leading to the destruction of the initial morphology and lattice structure and the loss of catalytic activity, which in turn dramatically reduces the service life of the membrane electrode (MEA). In contrast, Cu 2+ / Cu (+0.3V vs NHE) has a higher anodic dissolution potential than Fe 2+ / Fe(-0.5V vs NHE),Co 2+ / Co(-0.2V vs NHE) and Ni 2+ / Ni (+0.1 V vs NHE), which indicates that Cu is more stable during ORR potential cycling and is difficult to dissolve in acidic electrolytes.

[0004] In addition, chlorides can poison the performance of PEMFCs. Since commercial Pt / C catalysts use Cl-containing Pt precursors such as chloroplatinic acid or potassium chloroplatinate during preparation, Cl elements still remain after batch preparation. -1 The presence of will poison the active sites of the catalyst, causing more H2O2 to be generated during the ORR process, and will also cause the catalyst to dissolve, thereby reducing the electrochemical active surface area.

[0005] In response to the above problems, the inventor of the present application made Chinese invention patent application No. CN202111084983.8, which discloses a method for preparing chlorine-free PtCu alloy nanocatalyst. The present application is a further research and improvement by the inventor based on the aforementioned application. Summary of the invention

[0006] The first aspect of the present invention discloses a method for preparing a chlorine-free PtCu / C catalyst with a hollow sphere structure, comprising the following steps:

[0007] ⑴ calcining the carbon carrier in a reducing atmosphere;

[0008] (2) dispersing the calcined carbon support in an alcohol-water mixed solution, adding an oxidant to carry out a hydrothermal reaction;

[0009] ⑶ Dispersing the carbon carrier after the hydrothermal reaction evenly in an alcohol-water mixed solution, and adjusting the pH to acidic to obtain a carbon carrier suspension;

[0010] (4) Adding Pt(NH3)4(OH)2 solution and Cu(NH3)4(OH)2 solution to the carbon support suspension, and then adding a reducing agent to obtain a chlorine-free PtCu / C catalyst, wherein PtCu is a nano hollow sphere structure.

[0011] In the present invention, after calcining the carbon carrier under a reducing atmosphere, the uneven oxygen-containing functional groups on its surface can be removed, which is beneficial to increase the graphitization degree of the carbon carrier, thereby improving the corrosion resistance. The subsequent addition of an oxidant for hydrothermal reaction can introduce more negatively charged oxygen-containing functional groups to the surface of the carbon carrier, and can also introduce carbon defects on the basis of calcination, which can provide a large number of metal particle anchoring sites. Adjusting the pH to acidic can provide a favorable environment for the adsorption of metal precursors. The positively charged Pt[NH3]4 2+ / Cu[NH3]4 2+ The strong electrostatic adsorption between the metal precursor ions and the negatively charged oxygen-containing functional groups on the carbon support can effectively anchor the metal precursor ions on the carbon support. Finally, a reducing agent is added to reduce the metal precursor ions to form a chlorine-free PtCu / C catalyst with a nano-hollow sphere structure.

[0012] Furthermore, Pt atoms are located in the outer layer of the hollow nanospheres, and Cu atoms are mainly distributed on the inner side of the hollow nanospheres. This structure can expose more Pt active sites, thereby improving the performance of the catalyst.

[0013] Furthermore, the size of the hollow nanospheres is less than 20 nm.

[0014] Furthermore, in step (1), the calcination temperature is 750-850°C and the calcination time is 1-3h. If the calcination temperature is too low, the carbon carrier in the catalyst may have a low degree of graphitization, poor conductivity and corrosion resistance, which is not conducive to ORR electrocatalysis; if the calcination temperature is too high, the carbon carrier may have a low degree of defects and lack metal particle anchoring points, thereby reducing the catalytic performance.

[0015] Furthermore, the alcohol-water mixed solution is a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 0.5 to 2:1.

[0016] Furthermore, in step (2), the hydrothermal reaction temperature is 180-200° C., and the hydrothermal time is 4-6 h.

[0017] Furthermore, in step (3), HNO3 is used to adjust the pH to 2-3.

[0018] Furthermore, the oxidant is H2O2, and the reducing agent is NaBH4.

[0019] Furthermore, the mass ratio of Pt to Cu in the chlorine-free PtCu / C catalyst is 1-3:1-3.

[0020] The second aspect of the present invention relates to the use of the chlorine-free PtCu / C catalyst obtained by the aforementioned preparation method in an ORR reaction.

[0021] The technical solution of the present invention has at least the following beneficial effects:

[0022] The electrocatalytic ORR activity of Pt-based catalysts is closely related to their microstructures. Among various forms, hollow or porous structures can significantly improve the catalytic activity of the catalyst. The present invention uses Pt(NH3)4(OH)2 and Cu(NH3)4(OH)2 as metal precursors. On the one hand, it eliminates the contamination of Cl ions in the chlorine-containing precursors of the prior art. On the other hand, combined with the pretreatment steps of the carbon carrier, PtCu nanoparticles with a hollow sphere structure can be obtained without adding additional templates or morphology control components. The Pt atoms are located in the outer layer of the hollow spheres, which is beneficial to improve the atomic utilization rate and expose a large number of catalytic sites, thereby increasing the electrochemically active surface area and improving the electrocatalytic activity of the catalyst.

[0023] In order to more clearly illustrate the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Example PtCu(N) / C R-F 、Comparative Example 1Pt(N) / C R-F 、Comparative Example 2Cu(N) / C R-FCatalyst and Comparative Example 3PtCu(Cl) / C R-F XRD characterization spectrum of the catalyst;

[0025] Figure 2a Example PtCu(N) / C R-F TEM image of the catalyst, 2b is its STEM image;

[0026] Figure 3a Example PtCu(N) / C R-F HR-TEM image of the catalyst, 3b is its HAADF-STEM image;

[0027] Figure 4 Middle: a is a comparative example 1Pt(N) / C R-F a is the TEM image of the catalyst, b is its HR-TEM image;

[0028] Figure 5 Middle: a is a comparative example 2Cu(N) / C R-F a is the TEM image of the catalyst, b is its HR-TEM image;

[0029] Figure 6 Middle: a is a comparative example 3PtCu(Cl) / C R-F a is the TEM image of the catalyst, b is its HR-TEM image;

[0030] Figure 7 It is C0, C F , C R , C R-F Support, and [Pt(NH3)4](OH)2 / [Cu(NH3)4](OH)2 and C R-F Fourier transform infrared spectroscopy (FTIR) of the freeze-dried powder after the carrier was mixed in aqueous solution;

[0031] Figure 8 It is C0, C F , C R-F Support, as well as [Pt(NH3)4](OH)2+[Cu(NH3)4](OH)2 and [Pt(NH3)4](OH)2+[Cu(NH3)4](OH)2+C R-F Zeta potential diagram;

[0032] Fig. 9 Example PtCu(N) / C R-F And comparative example 1Pt(N) / C R-F Pt 4f XPS pattern of the catalyst;

[0033] Fig.10CV graphs of the cyclic voltammetry curves of the embodiments, comparative examples 1-3 and commercial Pt / C catalysts under N2 saturated conditions;

[0034] Fig.11 It is a comparison diagram of the linear sweep voltammetry (LSV) curves of the embodiment, comparative examples 1-3 and commercial Pt / C catalyst;

[0035] Fig.12 is the Tafel slope curve of the embodiment, comparative examples 1-3 and the commercial Pt / C catalyst;

[0036] Fig.13 is a graph of the electron transfer number and H2O2 yield of Example, Comparative Example 1 and commercial Pt / C catalyst;

[0037] Fig.14 Example PtCu(N) / C R-F LSV curve and KL diagram of the catalyst at different speeds;

[0038] Fig.15 Example PtCu(N) / C R-F LSV curves of the catalyst and commercial Pt / C catalyst in GDE half-cell;

[0039] Fig.16 Example PtCu(N) / C R-F EIS impedance graph of the catalyst and commercial Pt / C catalyst;

[0040] Fig.17 Example PtCu(N) / C R-F Comparison of the chronoamperometric curves (it) of the catalyst and the commercial Pt / C catalyst. DETAILED DESCRIPTION

[0041] The embodiment of the present invention provides a method for preparing a chlorine-free PtCu / C catalyst with a hollow sphere structure. The preparation method uses a chlorine-free metal precursor, utilizes the strong electrostatic adsorption between the positively charged metal precursor ions and the negatively charged oxygen-containing functional groups on the carbon carrier, and combines the impregnation reduction method to obtain a chlorine-free PtCu / C catalyst with a hollow sphere structure. The PtCu particles in the catalyst are hollow sphere structures, which can improve the atomic utilization rate and expose a large number of catalytic sites, and have extremely high electrocatalytic activity and stability.

[0042] The preparation method of the embodiment comprises the following steps:

[0043] ⑴ Place an appropriate amount of carbon carrier, such as carbon powder BP2000, in a H2 / Ar atmosphere and calcine it; wherein the calcination temperature is 750-850°C (e.g. 800°C), the calcination time is 1-3h (e.g. 2h), and the volume ratio of H2 in the H2 / Ar gas is 5%.

[0044] (2) The calcined carbon carrier is dispersed in an alcohol-water mixed solution, and an oxidant is added to carry out a hydrothermal reaction; specifically, the alcohol-water mixed solution can be a mixed solution of ethanol and water, and the volume ratio of ethanol to water is 0.5 to 2:1, preferably 1:1; the hydrothermal reaction temperature is 180 to 200°C (e.g., 200°C), and the hydrothermal time is 4 to 6h (e.g., 6h). The oxidant can be nitric acid, nitric acid-sulfuric acid, H2O2, etc., preferably H2O2.

[0045] ⑶ The carbon carrier after the hydrothermal reaction is evenly dispersed in an alcohol-water mixed solution, and the pH is adjusted to 2-3 to obtain a black carbon carrier suspension; specifically, the pH is adjusted with 0.1 mol / L HNO3.

[0046] (4) Mix the Pt(NH3)4(OH)2 solution and the Cu(NH3)4(OH)2 solution in a predetermined ratio and add the black suspension dropwise. Then add an appropriate amount of a reducing agent such as NaBH4. After the reaction, wash and filter with pure water. After freeze-drying, a chlorine-free PtCu / C catalyst with a hollow spherical structure is obtained.

[0047] Hereinafter, the present invention is described in more detail based on specific examples and comparative examples.

[0048] Example: PtCu(N) / C R-F Catalyst preparation

[0049] ⑴ First, 100 mg of carbon powder BP2000 (C0) was placed in a tube furnace and calcined at 800 ° C in Ar / H2 atmosphere for 2 h to obtain C R .

[0050] ⑵C R Ultrasonic dispersion was performed in a mixed solution of 25 mL pure water and 25 mL anhydrous ethanol for 1 h, and then 2 mL H2O2 was added to the obtained black suspension. After stirring for 10 min, it was transferred to a 100 mL polytetrafluoroethylene sealed autoclave and heated at 200 ° C for 6 h. After cooling to room temperature, it was filtered and washed with pure water, and finally dried in a vacuum drying oven for 2 h to obtain C R-F . R Replace with C0, and the other steps are the same to obtain carrier C F .

[0051] ⑶ Weigh 10 mg C R-F The mixture was added into a mixture of 40 mL pure water and 40 mL ethanol and ultrasonicated for 3 h. 0.1 mol / L HNO3 solution was added dropwise into the solution to adjust the pH to 2-3 to obtain a black suspension.

[0052] ⑷ Add 60 μL of 0.05 g / mL [Pt(NH3)4](OH)2 solution and 100 μL of 0.05 g / mL [Cu(NH3)4](OH)2 solution to 10 mL of aqueous solution, mix well and then add dropwise to the above black suspension, stir well and ultrasonicate for 30 min and stir for 2 h, then add 20 mL of 20 mmol / L NaBH4 solution to the solution, let stand for 30 min, stir for 4 h, wash with pure water, filter and put in the refrigerator for 48 h and freeze-dry to obtain the catalyst PtCu(N) / C R-F .

[0053] Comparative Example 1: Pt(N) / C R-F Catalyst preparation

[0054] The difference between this comparative example and the embodiment is that only [Pt(NH3)4](OH)2 solution is added in this comparative example.

[0055] ⑴ First, 100 mg of carbon powder BP2000 (C0) was placed in a tube furnace and calcined at 800 ° C in Ar / H2 atmosphere for 2 h to obtain C R .

[0056] ⑵C R Dispersed in a mixed solution of 25 mL pure water and 25 mL anhydrous ethanol, ultrasonically treated for 1 h, then 2 mL H2O2 was added to the obtained black suspension, stirred for 10 min, transferred to a 100 mL polytetrafluoroethylene sealed autoclave, and heated at 200 ° C for 6 h. After cooling to room temperature, filtered and washed with pure water, and finally dried in a vacuum drying oven for 2 h to obtain C R-F .

[0057] ⑶ Weigh 10 mg C R-F The mixture was added into a mixture of 40 mL pure water and 40 mL ethanol and ultrasonicated for 3 h. 0.1 mol / L HNO3 solution was added dropwise into the solution to adjust the pH to 2-3 to obtain a black suspension.

[0058] ⑷ Add 60 μL of 0.05 g / mL [Pt(NH3)4](OH)2 solution to 10 mL of aqueous solution, mix well, then add dropwise to the above black suspension, stir well, ultrasonicate for 30 min and stir for 2 h, then add 20 mL of 20 mmol / L NaBH4 solution to the solution, let stand for 30 min, stir for 4 h, wash with pure water, filter, put in the refrigerator for 48 h and freeze-dry to obtain the catalyst Pt(N) / C R-F .

[0059] Comparative Example 2: Cu(N) / C R-F Catalyst preparation

[0060] The difference between this comparative example and the embodiment is that only [Cu(NH3)4](OH)2 solution is added in this comparative example.

[0061] ⑴ First, 100 mg of carbon powder BP2000 (C0) was placed in a tube furnace and calcined at 800 ° C in Ar / H2 atmosphere for 2 h to obtain C R .

[0062] ⑵C R Dispersed in a mixed solution of 25 mL pure water and 25 mL anhydrous ethanol, ultrasonically treated for 1 h, then 2 mL H2O2 was added to the obtained black suspension, stirred for 10 min, transferred to a 100 mL polytetrafluoroethylene sealed autoclave, and heated at 200 ° C for 6 h. After cooling to room temperature, filtered and washed with pure water, and finally dried in a vacuum drying oven for 2 h to obtain C R-F .

[0063] ⑶ Weigh 10 mg C R-F The mixture was added into a mixture of 40 mL pure water and 40 mL ethanol and ultrasonicated for 3 h. 0.1 mol / L HNO3 solution was added dropwise into the solution to adjust the pH to 2-3 to obtain a black suspension.

[0064] ⑷ Add 100 μL of 0.05 g / mL [Cu(NH3)4](OH)2 solution to 10 mL of aqueous solution, mix well, then add dropwise to the above black suspension, stir well, ultrasonicate for 30 min and stir for 2 h, then add 20 mL of 20 mmol / L NaBH4 solution to the solution, let stand for 30 min, stir for 4 h, wash with pure water, filter, put in the refrigerator for 48 h and freeze-dry to obtain the catalyst Cu(N) / C R-F .

[0065] Comparative Example 3: PtCu(Cl) / C R-F Catalyst preparation

[0066] The difference between this comparative example and the embodiment is that in this comparative example, the [Pt(NH3)4](OH)2 solution is replaced with 495 μL of a 0.0075 g / mL H2PtCl6 solution.

[0067] ⑴ First, 100 mg of carbon powder BP2000 (C0) was placed in a tube furnace and calcined at 800 ° C in Ar / H2 atmosphere for 2 h to obtain C R .

[0068] ⑵C RDispersed in a mixed solution of 25 mL pure water and 25 mL anhydrous ethanol, ultrasonically treated for 1 h, then 2 mL H2O2 was added to the obtained black suspension, stirred for 10 min, transferred to a 100 mL polytetrafluoroethylene sealed autoclave, and heated at 200 ° C for 6 h. After cooling to room temperature, filtered and washed with pure water, and finally dried in a vacuum drying oven for 2 h to obtain C R-F .

[0069] ⑶ Weigh 10 mg C R-F The mixture was added into a mixture of 40 mL pure water and 40 mL ethanol and ultrasonicated for 3 h. 0.1 mol / L HNO3 solution was added dropwise into the solution to adjust the pH to 2-3 to obtain a black suspension.

[0070] (4) Add 495 μL of 0.0075 g / mL H2PtCl6 solution and 100 μL of 0.05 g / mL [Cu(NH3)4](OH)2 solution to 10 mL of aqueous solution, mix well, add dropwise to the above black suspension, stir well, ultrasonicate for 30 min and stir for 2 h, then add 20 mL of 20 mmol / L NaBH4 solution to the solution, let stand for 30 min, stir for 4 h, wash with pure water, filter, put in the refrigerator for 48 h and freeze-dry to obtain the catalyst PtCu(Cl) / C R-F .

[0071] Morphology, size and phase analysis of examples and comparative examples

[0072] Figure 1 Example PtCu(N) / C R-F 、Comparative Example 1Pt(N) / C R-F 、Comparative Example 2Cu(N) / C R-F And comparative example 3PtCu(Cl) / C R-F XRD patterns of the catalysts. By comparing the PDF cards, we can see that the XRD diffraction peaks of the four catalysts all have typical face-centered cubic (FCC) characteristics. R-F The diffraction peak of the catalyst shifts to a higher 2θ angle because the introduction of Cu causes some atoms to form alloys and the lattice constant decreases.

[0073] Figure 2a and b are examples of PtCu(N) / C R-F The TEM and STEM images of the catalyst show that the carbon carrier is loaded with many interconnected hollow spherical PtCu particles with a particle size range of 5-12 nm. Figure 3a and b are examples of PtCu(N) / C R-F HR-TEM and HAADF-STEM images of the catalyst. Figure 3aIt can be seen that there are lattice fringes in different directions on the hollow spherical nanoparticles, among which the lattice fringes with a spacing of 0.202 nm correspond to the (111) crystal plane of Cu, and the lattice fringes with a spacing of 0.224 nm correspond to the (111) crystal plane of Pt. Figure 3b It can be seen that the brightest area on the outer layer of the hollow sphere is Pt atoms, the darker area on the inner side is Cu atoms, and the small area in the middle is PtCu alloy, which is consistent with the XRD characterization results.

[0074] Figure 4 a and b are comparative examples 1Pt(N) / C R-F From the TEM and HR-TEM images of the catalyst, it can be seen that the Pt morphology in the catalyst is similar to a flower-like structure and is a non-hollow structure. The lattice fringe spacing of 0.197 nm corresponds to the (200) crystal plane of Pt, and the lattice fringe spacing of 0.227 nm corresponds to the (111) crystal plane of Pt. Figure 5 a and b are comparative examples 2Cu(N) / C R-F From the TEM and HR-TEM images of the catalyst, it can be seen that the morphology of Cu in the catalyst is a spherical non-hollow structure, and the lattice fringe spacing of 0.199nm corresponds to the (111) crystal plane of Cu.

[0075] According to the test results of inductively coupled plasma atomic emission spectrometry (ICP-OES), the PtCu(N) / C R-F The mass ratio of Pt in the catalyst is 6.51%, the mass ratio of Cu is 5.75%, and the mass ratio of Pt (N) / C in the comparative example 1 is 5.75%. R-F The mass ratio of Pt in the catalyst is 10.8%, and the mass ratio of Cu(N) / C in the comparative example 2 is 10.8%. R-F The mass ratio of Cu in the catalyst is 10.6%.

[0076] Figure 6 a and b are comparative examples 3PtCu(Cl) / C R-F The TEM and HR-TEM images of the catalyst show that the carbon support is loaded with non-hollow spherical PtCu nanoparticles. The lattice fringe spacing of 0.201nm corresponds to the (111) crystal plane of Cu, and the lattice fringe spacing of 0.225nm corresponds to the (111) crystal plane of Pt. R-F With PtCu(Cl) / C R-F The differences in morphology and dispersion among the catalysts are mainly attributed to the different chemical structures of the Pt precursors.

[0077] Figure 7 It is C0, C F , C R , C R-F Support, and [Pt(NH3)4](OH)2 / [Cu(NH3)4](OH)2 and CR-F Fourier transform infrared spectrum (FTIR) of freeze-dried powder after mixing in aqueous solution. In the figure, C0 is at 3625cm -1 、1567cm -1 、1100cm -1 The characteristic peaks on the left and right are hydroxyl group (-OH), C=C stretching vibration and CO single bond. R At 3600cm -1 The -OH peaks on the left and right disappeared, indicating that the oxygen-containing functional groups on C0 were basically reduced after heat treatment. R-F At 3500cm -1 A stronger -OH peak reappears at the surface, indicating that surface functionalization with H2O2 after heat treatment can introduce more oxygen-containing functional groups into the carbon support. R-F The freeze-dried powder mixed in aqueous solution was -1 The characteristic peak at 3500cm is the stretching vibration of CN. -1 The -OH peak around 1100cm -1 The CO single bonds on the left and right sides have basically disappeared, indicating that the [Pt(NH3)4](OH)2 precursor and C R-F There is a strong electrostatic adsorption between the oxygen-containing functional groups on [Cu(NH3)4](OH)2 and C R-F The freeze-dried powder mixed in aqueous solution was -1 The characteristic peaks of CO single bonds around the left and right sides weakened, and the peak positions shifted, confirming that the [Cu(NH3)4](OH)2 precursor and C R-F There is also a strong electrostatic adsorption between the oxygen-containing functional groups on the surface.

[0078] Figure 8 It is C0, C F , C R-F Support, as well as [Pt(NH3)4](OH)2+[Cu(NH3)4](OH)2 and [Pt(NH3)4](OH)2+[Cu(NH3)4](OH)2+C R-F Zeta potential diagram. As can be seen from the figure, the potential of C0 is -4.7mV, C F The potential is -6.8mV, C R-F The potential of C is -7.3 mV, indicating that functionalization with H2O2 after heat treatment / calcination is beneficial to R-F More negatively charged functional groups are introduced on the surface of the carrier. In addition, the potential of [Pt(NH3)4](OH)2+[Cu(NH3)4](OH)2 is 5.6mV, and the addition of C R-F The potential measured in the dispersion is -2.9 mV, which further indicates that Pt(NH3)42+ / Cu(NH3)4 2+ With C R-F There is a strong electrostatic adsorption between the negatively charged oxygen-containing functional groups.

[0079] Fig. 9 For example, PtCu(N) / C R-F And comparative example 1Pt(N) / C R-F Pt 4f XPS graph of the catalyst shows PtCu(N) / C R-F The Pt 4f peaks are compared with those of Pt(N) / C R-F It shifts toward the direction of low binding energy, which may be due to the ligand effect between Pt and Cu. Since the electronegativity of Cu is smaller than that of Pt, there is a charge transfer from Cu to Pt between Pt and Cu, which increases the electron density of Pt atoms and thus leads to a decrease in binding energy.

[0080] Catalytic performance testing

[0081] RDE test conditions: The test was conducted in a 0.5 mol / L H2SO4 solution saturated with O2 using a three-electrode system; the reference electrode was an Ag / AgCl electrode and the counter electrode was a platinum electrode. The rotation speed was 1600 rpm and the catalyst loading was 2 mg cm -2 .

[0082] GDE half-cell test conditions: A three-electrode system was used. The catalyst ink was coated on carbon cloth to prepare GDE as the working electrode, the Pt sheet connected to the carbon rod was the counter electrode, and the Ag / AgCl (saturated KCl solution) electrode was the reference electrode. The catalyst loading was 2 mg cm -2 , the electrolyte is 0.5mol / L H2SO4 solution.

[0083] Fig.10 The CV curves of the examples, comparative examples 1-3 and commercial Pt / C catalysts under N2 saturation conditions are shown in Figure 1. The peaks at 0.4-0.8V in the figure belong to the redox peak of Pt, and PtCu(N) / C R-F The H adsorption / desorption peak area of ​​the catalyst is the largest, indicating that PtCu(N) / C R-F The hollow sphere structure can provide a larger electrochemical active surface area for ORR.

[0084] Fig.11 The linear sweep voltammetry (LSV) curves of the examples, comparative examples 1-3 and commercial Pt / C catalysts are compared. R-F The catalyst exhibited a higher limiting current density (j L =4.8mAcm -2 ), starting potential (Eonset =0.961V) and half-wave potential (E 1 / 2 =0.827V), which is significantly higher than that of Comparative Examples 1-3 and commercial Pt / C catalysts, indicating that PtCu(N) / C R-F The PtCu alloy hollow sphere structure of the catalyst is beneficial to improving the catalytic activity of ORR.

[0085] Fig.12 is the Tafel slope curve of the embodiment, comparative examples 1-3 and commercial Pt / C catalyst, wherein the PtCu(N) / C of the embodiment is R-F The catalyst exhibits the smallest slope, indicating that its ORR catalytic reaction rate is the fastest and exhibits the best ORR reaction activity.

[0086] Fig.13 The electron transfer number and H2O2 yield of Example 1, Comparative Example 1 and commercial Pt / C catalyst are shown in Figure 2. R-F The H2O2 yield of the catalyst is almost zero, PtCu(N) / C R-F 、Pt(N) / C R-F The electron transfer number of PtCu(N) / C is slightly higher than that of commercial Pt / C catalysts. R-F The electron transfer number of the catalyst is closest to 4, which further indicates that PtCu(N) / C R-F The catalyst has higher catalytic activity for ORR.

[0087] Fig.14 Example PtCu(N) / C R-F The LSV curves and KL diagrams of the catalyst at different speeds show that the ORR current density increases with increasing speed, indicating that the ORR process is controlled by O2 diffusion. R-F The electron transfer number of the catalyst is 4. This indicates that PtCu(N) / C R-F The ORR on the catalyst follows a four-electron reaction pathway, and O2 is directly reduced to H2O on the PtCu(N) / CR-F catalyst surface, which is consistent with the test results of RRDE.

[0088] Fig.15 Example PtCu(N) / C R-F LSV curves of the catalyst and commercial Pt / C catalyst in GDE half-cell. PtCu(N) / C R-F The LSV curves of the Pt / C ... -2 The overpotential difference is 137 mV, and a lower overpotential is beneficial to promoting mass transfer efficiency.

[0089] Fig.16 Example PtCu(N) / C R-F The EIS impedance diagram of the catalyst and the commercial Pt / C catalyst shows that PtCu(N) / C R-F The arc radius of PtCu(N) / C is significantly smaller than that of commercial Pt / C. R-F The charge transfer resistance is lower than that of commercial Pt / C, and the mass transfer and conductivity are faster.

[0090] Fig.17 The PtCu(N) / C prepared in Example R-F Comparison of the chronoamperometric curves (it) of the catalyst and the commercial Pt / C catalyst. PtCu(N) / C R-F After 20,000 s of stability testing, the current of the catalyst decreased by 15.8%, while that of the commercial Pt / C catalyst decreased by 20.8%, indicating that PtCu(N) / C R-F The catalyst has better stability.

[0091] In summary, the PtCu nanoparticles in the chlorine-free PtCu / C catalyst prepared by the present invention are hollow sphere structures, which can provide higher atomic utilization and larger electrochemical active surface area, and improve the electrocatalytic activity of the catalyst. PtCu particles are used as reaction active sites, and the synergistic effect and ligand effect between Pt and Cu atoms can play a significant regulatory role, change the electronic structure of Pt, cause a negative shift in the d-band center of Pt, weaken the adsorption strength of oxygen-containing intermediates on Pt sites during the ORR process, and reduce the reaction energy barrier of the catalyst in the oxygen reduction reaction, so that the catalyst has higher electrocatalytic activity and stability for the ORR reaction.

[0092] Although the present invention is described above through specific embodiments, it should be understood that any equivalent improvements made by ordinary technicians in this field without departing from the scope of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a chlorine-free PtCu / C catalyst with a hollow sphere structure, characterized in that The steps include: ⑴ calcining the carbon carrier in a reducing atmosphere; (2) dispersing the calcined carbon support in an alcohol-water mixed solution, adding an oxidant to carry out a hydrothermal reaction; ⑶ Dispersing the carbon carrier after the hydrothermal reaction evenly in an alcohol-water mixed solution, and adjusting the pH to acidic to obtain a carbon carrier suspension; (4) Adding Pt(NH3)4(OH)2 solution and Cu(NH3)4(OH)2 solution to the carbon support suspension, and then adding a reducing agent to obtain a chlorine-free PtCu / C catalyst, wherein PtCu is a nano hollow sphere structure.

2. The preparation method according to claim 1, characterized in that: The Pt atoms are located in the outer layer of the hollow nanosphere.

3. The preparation method according to claim 1, characterized in that: The size of the hollow nanospheres is less than 20 nm.

4. The preparation method according to claim 1, characterized in that: In step (1), the calcination temperature is 750-850° C. and the calcination time is 1-3 h.

5. The preparation method according to claim 1, characterized in that: The alcohol-water mixed solution is a mixed solution of ethanol and water, wherein the volume ratio of ethanol to water is 0.5 to 2:

1.

6. The preparation method according to claim 1, characterized in that: In step (2), the hydrothermal reaction temperature is 180-200° C. and the time is 4-6 h.

7. The preparation method according to claim 1, characterized in that: In step (3), HNO3 is used to adjust the pH to 2-3.

8. The preparation method according to claim 1, characterized in that: The oxidizing agent is H2O2, and the reducing agent is NaBH4.

9. The preparation method according to claim 1, characterized in that: The mass ratio of Pt to Cu in the chlorine-free PtCu / C catalyst is 1-3:1-3.

10. Use of the chlorine-free PtCu / C catalyst obtained by the preparation method according to any one of claims 1 to 9 in an ORR reaction.

Citation Information

Patent Citations

  • Pt-Nafion / C catalyst and preparation method and application for same

    CN103120960A

  • Method for preparing N-rGO loaded PtCu alloy nano-catalyst

    CN113903927A

  • Hydrogen fuel cell alloy catalyst and preparation method thereof

    CN116387537A

  • Preparation method of surface nitrogen modified fuel cell carbon carrier

    CN118412481A

Cited By

  • Method for improving oxygen reduction reaction performance of nano-metal-based electrocatalyst, prepared modified electrocatalyst and application of modified electrocatalyst

    CN121237910A